Radical Constructivism - von Glasersfeld, Ernst (Taylor & Francis Group, 1995)
First Published in 1995.In the past decade or two, the most important theoretical perspective to emerge in mathematics education has been that of constructivism.This burst onto the international scene at the controversial Eleventh International Conference on the Psychology of Mathematics Education in Montreal in the summer of 1987.